Horrid Henry and the mummy's curse - Simon, Francesca; Ross, Tony (Naperville, Ill. : Sourcebooks Jabberwocky, 2009)
Collects four stories in which Horrid Henry gets involved in various schemes while collecting gizmos, having trouble with his spelling homework, starting a rumor about a shark in the swimming pool, and convincing his friend Peter that the mummy kit he won at the museum is cursed.
Originally published: Great Britain : Orion Children's Books, 2000.
2.9
K-3
Keywords: Horrid Henry (Fictitious character) -- Juvenile fiction; Human behavior -- Juvenile fiction; Behavior -- Fiction; Horrid Henry (Fictitious character) -- Fiction; Horrid Henry (Fictional character) -- Fiction; Human behavior -- Fiction